Pemilihan Supplier Apel Berbasis Green Procurement dengan Metode AHP (Studi Kasus: Toko Malang Strudel) - Abdul Rahim; Armey Marsusvita; Sesmita Sari (Jurnal Teknologi dan Industri Pertanian Indonesia, 2023)
The development of industry and consumer concern for the environment is increasing as well as the issue of industrial concepts that are environmentally sound. So that forces the industry to make adjustments to the concept of green industries in every business, including procurement, which is better known as green procurement. Supplier selection is an important decision-making problem in order to get suppliers who can increase the company's competitiveness. This research was conducted at the Strudel cake shop in Malang to evaluate and select suppliers of apples based on green procurement with the AHP method. The criteria used are 6 criteria, namely quality, technology capability, pollution control, environment management, green product, and green competence. Each criterion has sub-criteria between 3 or 4 sub-criteria. The number of sub-criteria is used to determine the RI value. The RI value is used to calculate the CR value of each criterion. The results of data processing show that the highest CR value is on the technology capability criteria and the lowest CR value is environment management.